Dispositional Factors and Sportsmanship in Italian Athletes - Flavio Ceglie (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
The research focused on dispositional factors determining fair play is a matter of debate. In this vein, sportsmanship has been considered to be a multidimensional construct reflecting how athletes are inclined to play sport. Previous investigations found significant associations between motivational orientations and sportsmanship. To date, little attention has been paid to the construct of the trait of self-control in predicting sportsmanship and to the role of gender differences in this relationship. This study analysed not only the associations between task and ego orientation, trait self-control and sportsmanship in order to determine the best predictor of sportsmanship, but also to verify whether the linkages were confirmed in the gender subgroups. Competitive level athletes (N=674, 387 males and 287 female; M=27.23 years, SD=10.01) completed a questionnaire including the scales of goal orientation, self-control and sportsmanship. Descriptive statistics, bivariate correlations, and regression analyses were applied to the data. The results indicated positive associations between task orientation, self-control and sportsmanship, and between task orientation and self-control. No significant association emerged between ego orientation and self-control in the total sample and in the gender subgroups. Sportsmanship was influenced positively by task orientation and age in all groups and negatively by ego orientation in the total sample and in the male group. A weak but significant relationship between trait self-control and sportsmanship was found only in the total sample. These findings suggested further analyses of the mediating/moderating role played by self-control in the indirect relationships between goal orientations and sportsmanship in relation to gender differences.